Cost of Production of Telenomus remus (Hymenoptera: Platygastridae) Grown in Natural and Alternative Hosts - Vieira, Natalia F. [UNESP]; Pomari-Fernandes, Aline; Lemes, Amanda A. F. [UNESP]; Vacari, Alessandra M. [UNESP]; De Bortoli, Sergio A. [UNESP]; Bueno, Adeney de Freitas (Oxford Univ Press Inc, 2017)
The study of the technical and economic aspects of rearing natural enemies is essential for its effective use as a biological control agent in the field. The aim of this study was to determine the cost of production of the parasitoid, Telenomus remus (Nixon; Hymenoptera: Platygastridae), reared in eggs of its natural host, Spodoptera frugiperda (J. E. Smith; Lepidoptera: Noctuidae), and the alternative host, Corcyra cephalonica (Stainton; Lepidoptera: Pyralidae). The insects were reared in accordance with their respective methodologies of laboratory rearing. The cost of production of this biocontrol agent is US$ 0.0004 when reared with S. frugiperda eggs and US$ 0.0002 with C. cephalonica eggs.
Keywords: Mass rearing; biological control; fall armyworm; rice moth; parasitoid